The effect of natural/human-made hazards on business establishments and their supply chains. (1st June 2021) - Thomas, Douglas; Helgeson, Jennifer
Abstract: This paper examines the impact of natural and human-made hazards on payroll, GDP, employment, and establishment survival/creation in the year of hazard occurrence in the U.S. economy and more specifically in the U.S. manufacturing/goods producing industry. Many of the papers that examine economic impacts of hazards consider upstream impacts of supply chain disruption. Measures of downstream impacts are often limited, particularly in measuring the short-term impacts. This paper examines how manufacturers and other establishments are impacted, at the industry and total economy level, by a disruption in supplies of goods with low substitutability, which is often referred to as the ripple effect. In this paper, eight models are developed to explore supply chain vulnerability, at the industry-level, to hazard events across geographic areas of the U.S. during the 2005 to 2016 time period. The most severe impacts are due to hazards in the manufacturing/goods industry supply chain, where payroll, GDP, and employment declined 2.9%, 3.9%, and 8.6%, respectively. For all establishments, payroll and employment declined 5.3% and 3.0%, respectively. The results further suggest that the compound effect of hazards through the supply chain possibly exceeds that of the local hazard (i.e., direct impact). This can create an incentive misalignment. The establishment that invests in mitigation efforts and experiences the hazard locally does not directly experience the majority of the net benefit. The findings also suggest there is a need to better understand the short-term downstream impacts from all hazards, especially at the aggregated national level.